2021
DOI: 10.11591/ijphs.v10i2.20722
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of Indonesian residents regarding COVID-19: A national cross-sectional survey

Abstract: <p>Coronavirus disease (COVID-19) infection has been a major public health-related issue worldwide, including Indonesia. The COVID-19 cases still escalating until this study finished in June 2020 due to the disease positively spreading from person to person. To reduce the spreading of the disease, investigating Indonesian’s knowledge, attitudes, and practice on COVID prevention and mitigation during the outbreak period was crucial. A survey cross-sectional was conducted and using social networking apps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
1
0
0
3
Order By: Relevance
“…In regard to health protective behavior to prevent the spreading of the virus, we found a high to moderate percentages of participants implementing cough and sneezing etiquettes, avoiding handshakes, physical distancing, staying at home, and wearing a mask. This findings is in line with a study involving 3,464 general population in Indonesia that found the majority of participants show good practices to prevent and mitigate the COVID-19 pandemic [40]. Protective behaviors that tend to be implemented less frequently were washing hands and doing regular exercise at home.…”
Section: Discussionsupporting
confidence: 89%
“…In regard to health protective behavior to prevent the spreading of the virus, we found a high to moderate percentages of participants implementing cough and sneezing etiquettes, avoiding handshakes, physical distancing, staying at home, and wearing a mask. This findings is in line with a study involving 3,464 general population in Indonesia that found the majority of participants show good practices to prevent and mitigate the COVID-19 pandemic [40]. Protective behaviors that tend to be implemented less frequently were washing hands and doing regular exercise at home.…”
Section: Discussionsupporting
confidence: 89%
“…Hasil ini serupa dengan hasil penelitian pada masyarakat di Indonesia, ditemukan bahwa karakteristik sosio-demografis, yaitu jenis kelamin, wilayah tempat tinggal saat ini, latar belakang pendidikan, jenis pekerjaan, agama, dan status perkawinan memiliki hubungan yang signifikan dengan pengetahuan tentang COVID-19. 14 Penelitian di Bangladesh juga menemukan hasil bahwa usia, tingkat pendidikan dan distribusi geografis memiliki hubungan yang signifikan terhadap pengetahuan. Responden yang memiliki latar belakang pendidikan dasar memiliki skor pengetahuan terendah dibandingkan dengan semua responden kelompok pendidikan lainnya.…”
Section: Pembahasanunclassified
“…Hasil ini bertolak belakang dengan penelitian di Indonesia yang menemukan bahwa jenis kelamin, latar belakang pendidikan, jenis pekerjaan, dan karakteristik agama menunjukkan korelasi yang signifikan terhadap sikap. 14 Responden setuju bahwa penderita hipertensi lebih rentan terkena COVID-19 (56,3%) dan kemungkinan tertular COVID-19 besar karena menderita hipertensi (53,6%). Hasil penelitian ini serupa dengan penelitian yang dilakukan oleh Huynh et al 12 bahwa mayoritas responden (90,8%) yang merupakan penderita penyakit kronis memiliki sikap yang positif terhadap COVID-19 dan 66,5% responden setuju bahwa mereka memiliki kemungkinan tertular COVID-19.…”
Section: Pembahasanunclassified
See 1 more Smart Citation